Role of ionic liquid and tin (IV) oxide nanoparticles on the ionic conductivity of biodegradable solid polymer electrolyte - Chong, Mee Yoke; Numan, Arshid; Evyan, Y.C.Y.; Cheng, W.H.; Wong, L.S.; Ramesh, Kasi; Ramesh, Subramaniam (Medwell Journals, 2018)
Solution casting technique is used to prepare solid polymer electrolyte (SPE) utilizing biodegradable hydroxyethyl cellulose (HEC) as host polymer and magnesium trifluoromethanesulfonate (MgTf2) salt as charge carrier. However, the performance of the SPE is hindered by it's low ionic conductivity at room temperature. Thus, room temperature ionic liquid, 1-ethyl-3-methylimidazolium trifluoromethane sulfonate (EMIMTf) and tin (IV) oxide (SnO2) nanoparticles have been added into the SPE to overcome the shortcomings. As a result, the room temperature ionic conductivity improved to 9.28 × 10-5 and 2.84 × × 10-4 S/cm upon addition of 40 wt.% EMIMTf ionic liquid and 2 wt.% of SnO2 nanoparticles, respectively. The conductivity-temperature plot shows that the transportation of ions in these films obey Arrhenius theory. The improvement of the ionic conductivity at room temperature for HSn2 makes it attractive for application to electrochemical devices.